Posterior lobules of the cerebellum and information processing speed at various stages of multiple sclerosis. Issue 2 (27th October 2016) - Moroso, Amandine; Ruet, Aurélie; Lamargue-Hamel, Delphine; Munsch, Fanny; Deloire, Mathilde; Coupé, Pierrick; Ouallet, Jean-Christophe; Planche, Vincent; Moscufo, Nicolas; Meier, Dominik S; Tourdias, Thomas; Guttmann, Charles R G; et al.
Abstract : Background: Cerebellar damage has been implicated in information processing speed (IPS) impairment associated with multiple sclerosis (MS) that might result from functional disconnection in the frontocerebellar loop. Structural alterations in individual posterior lobules, in which cognitive functioning seems preponderant, are still unknown. Our aim was to investigate the impact of grey matter (GM) volume alterations in lobules VI to VIIIb on IPS in persons with clinically isolated syndrome (PwCIS), MS (PwMS) and healthy subjects (HS). Methods: 69 patients (37 PwCIS, 32 PwMS) and 36 HS underwent 3 T MRI including 3-dimensional T1-weighted MRIs. Cerebellum lobules were segmented using SUIT V.3.0 to estimate their normalised GM volume. Neuropsychological testing was performed to assess IPS and main cognitive functions. Results: Normalised GM volumes were significantly different between PwMS and HS for the right (p<0.001) and left lobule VI (p<0.01), left crus I, right VIIb and entire cerebellum (p<0.05 for each comparison) and between PwMS and PwCIS for all lobules in subregions VI and left crus I (p<0.05). IPS, attention and working memory were impaired in PwMS compared with PwCIS. In the whole population of patients (PwMS and PwCIS), GM loss in vermis VI (R 2 =0.36; p<0.05 when considering age and T2 lesion volume as covariates) were associated with IPS impairment. Conclusions: GM volume decrease in posterior lobules (especially vermis VI) was associated with reduced IPS. Our results suggest a significant impact of posterior lobules pathology in corticocerebellar loop disruption resulting in automation and cognitive optimisation lack in MS. Trial registration: Clinicaltrail NCT01207856, NCT01865357 ; Pre-results.